1992
DOI: 10.1103/physrevlett.68.3567
|View full text |Cite
|
Sign up to set email alerts
|

Density redistribution in a microsecond-conduction-time plasma opening switch

Abstract: The first measurements of the line-integrated electron density in a coaxial microsecond-conductiontime plasma opening switch during switch operation are presented. Current conduction is observed to cause a radial redistribution of the switch plasma, with a large decrease in axial line density over most of the radial extent of the switch. A local reduction in line density of more than an order of magnitude occurs by the time opening begins. It is hypothesized that this density reduction allows the switch to ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(18 citation statements)
references
References 7 publications
2
16
0
Order By: Relevance
“…This observation supports our conjecture that also the relatively slow, nonaxial carbon motion, occurring after the arrival of the magnetic field front, contributes to the density drop. Such a nonaxial plasma motion, possibly resulting in local density minima, might be related to interferometric line-integrated measurements of the electron density 10,40,41 and to results of 2D numerical simulations ͑e.g., Ref. 42͒ that show the development of a gap or a density ''saddle'' in the plasma.…”
Section: Electron Density Distributionmentioning
confidence: 99%
“…This observation supports our conjecture that also the relatively slow, nonaxial carbon motion, occurring after the arrival of the magnetic field front, contributes to the density drop. Such a nonaxial plasma motion, possibly resulting in local density minima, might be related to interferometric line-integrated measurements of the electron density 10,40,41 and to results of 2D numerical simulations ͑e.g., Ref. 42͒ that show the development of a gap or a density ''saddle'' in the plasma.…”
Section: Electron Density Distributionmentioning
confidence: 99%
“…Methods based on interferometry 7 and emission spectroscopy, 8 highly advantageous for this purpose, suffer from the ambiguity caused by the measurement integration along the line of sight. For spectroscopic measurements, spatial resolution along the line of sight can be obtained by locally doping the plasma with selected species.…”
Section: Introductionmentioning
confidence: 99%
“…30 This observation was consistent with earlier line-integrated density measurement in similar systems. 32,33 The spatially resolved spectroscopic measurements showed that part of the plasma is indeed penetrated by the magnetic field and remains behind the propagating field front. The rise in the density was mainly attributed to the effect of the proton-plasma reflection.…”
mentioning
confidence: 99%